2014
DOI: 10.3389/fncom.2014.00050
|View full text |Cite
|
Sign up to set email alerts
|

Distributed organization of a brain microcircuit analyzed by three-dimensional modeling: the olfactory bulb

Abstract: The functional consequences of the laminar organization observed in cortical systems cannot be easily studied using standard experimental techniques, abstract theoretical representations, or dimensionally reduced models built from scratch. To solve this problem we have developed a full implementation of an olfactory bulb microcircuit using realistic three-dimensional (3D) inputs, cell morphologies, and network connectivity. The results provide new insights into the relations between the functional properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 46 publications
2
54
0
Order By: Relevance
“…GENESIS [42], MOOSE [28], [46], and NEURON [40] are simulators that aspire to the largest multiscale range, from molecular [22], [47], [48] to large networks [49], [50], with the ability to simulate across these multiple scales [51]. These simulators generally encourage the use of multicompartmental models of neurons, utilizing neuroanatomically-acquired dendritic tree morphologies approximated as tree-structured collections of frusta and cylinders.…”
Section: Neuroscience Simulatorsmentioning
confidence: 99%
“…GENESIS [42], MOOSE [28], [46], and NEURON [40] are simulators that aspire to the largest multiscale range, from molecular [22], [47], [48] to large networks [49], [50], with the ability to simulate across these multiple scales [51]. These simulators generally encourage the use of multicompartmental models of neurons, utilizing neuroanatomically-acquired dendritic tree morphologies approximated as tree-structured collections of frusta and cylinders.…”
Section: Neuroscience Simulatorsmentioning
confidence: 99%
“…Breakthrough experiments identified the odor receptor molecules [22] and showed that subsets of receptor cells expressing the same receptor gene project to differing sites in the glomerular layer, thus supporting the concept that space plays a role in encoding odor molecules. We are constructing computational models in three dimensions to gain further insight into how these images are formed within the olfactory bulb [23].…”
Section: Mechanisms For Flavor Images and Flavor Biomechanicsmentioning
confidence: 73%
“…Based on tracing studies, mitral/tufted cells associated with a single glomerulus display a broader anatomical distribution and long-range lateral processes within the EPL [32, 45]. The distance of periglomearular/tufted cell bodies from their glomerulus of origin is short, an average distance of 69 μm, with some cells extending as far as 150 μm [32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the average distance of mitral/tufted cell bodies from the glomerular midline is 111–116 μm [32], with 80% of the cells found within 111 μm [33, 46]. Mitral/tufted cell lateral dendrites, however, project approximately 750 μm from the cell bodies [45], with some extending as far as 1500 μm across the MOB [4648]. This suggests lateral dendrite engagement from glomerular stimulation produces enough neural activity to elicit a significant metabolic demand.…”
Section: Discussionmentioning
confidence: 99%